2019
DOI: 10.21522/tijph.2013.07.02.art017
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Culture among Health Workers in Addis Ababa regional Hospitals, Ethiopia

Abstract: Background: Improving patient safety highly depends on achieving a culture that supports health workers to report their errors without the fear of punishment. Despite policy emphasis on patient safety in Ethiopia only little studies examine the perception of health workers on patient safety. Objective: The main objective of this study was to assess the magnitude of patient safety culture and associated factors among health workers in Addis Ababa regional hospitals. Methods: Facility based cross sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…The overall level of the PSC of this study is higher when compared with the study conducted in Addis Ababa, 23 and Bale Zone hospital of Ethiopia. 26 This might be due to the difference in the study setting and the small sample size.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The overall level of the PSC of this study is higher when compared with the study conducted in Addis Ababa, 23 and Bale Zone hospital of Ethiopia. 26 This might be due to the difference in the study setting and the small sample size.…”
Section: Discussioncontrasting
confidence: 73%
“… 14–22 In Ethiopia studies conducted on Nurses showed that the overall patient safety culture ranged from 44%-58%. 23–27 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NOS score for the articles, which are included in this systematic review and meta-analysis, ranged from five to nine. Two of the studies 19,32 scored as satisfactory, 14 studies 12,18,[28][29][30][31][33][34][35][36][37][38][39] were scored as good, two studies 10,21 were scored as very good. Two studies 15,20 scored ≤5 of the quality assessment criteria and were excluded from the final analysis.…”
Section: Methodological Quality and Risk Of Biasmentioning
confidence: 99%
“…All the included 17 studies were cross-sectional in their study design. The overall data regarding the magnitude of labor pain management practices was obtained from different parts of Ethiopia: four studies from each 10,12,21,28 and Oromia, [29][30][31][32] three studies from South Nations and Nationalities People region (SNNPR), [33][34][35] two studies from each Addis Ababa 36,37 and Sidama, 19,38 one study from each Harari 18 and Tigray 39 regions. The data collection method employed in two of the studies 12,39 was interviewer administered while the remaining 15 studies used self-administered questionnaire.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%